Hospital organisation, management, and structure for prevention of health-care-associated infection: a systematic review and expert consensus. Issue 2 (February 2015) - Zingg, Walter; Holmes, Alison; Dettenkofer, Markus; Goetting, Tim; Secci, Federica; Clack, Lauren; Allegranzi, Benedetta; Magiorakos, Anna-Pelagia; Pittet, Didier; for the systematic review and evidence-based guidance on organization of hospital infection control programmes (SIGHT) study group, †
Summary Despite control efforts, the burden of health-care-associated infections in Europe is high and leads to around 37 000 deaths each year. We did a systematic review to identify crucial elements for the organisation of effective infection-prevention programmes in hospitals and key components for implementation of monitoring. 92 studies published from 1996 to 2012 were assessed and ten key components identified: organisation of infection control at the hospital level; bed occupancy, staffing, workload, and employment of pool or agency nurses; availability of and ease of access to materials and equipment and optimum ergonomics; appropriate use of guidelines; education and training; auditing; surveillance and feedback; multimodal and multidisciplinary prevention programmes that include behavioural change; engagement of champions; and positive organisational culture. These components comprise manageable and widely applicable ways to reduce health-care-associated infections and improve patients' safety.